Oxide film layer and surface-treatment aluminum material

An oxide film layer with a specific oxygen and aluminum composition, formed using advanced anodizing and sealing techniques, addresses thermal cracking issues in aluminum-based vacuum components, ensuring high-temperature stability and improved semiconductor manufacturing.

JP2025018200AInactive Publication Date: 2025-02-06CHUGOKU DENKA INDS
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023121709
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing aluminum-based vacuum device components suffer from thermal expansion issues, leading to crack formation in oxide film layers at high temperatures, which can cause defects in semiconductor wafers.

Method used

An oxide film layer composed of 73±2% oxygen and 27% aluminum, formed through anodizing with a higher voltage and subsequent sealing with ultrapure water vapor, creating an amorphous material that resists cracking up to 500°C.

Benefits of technology

The oxide film layer exhibits excellent heat resistance, preventing cracks at temperatures between 150°C and 500°C, reducing particle generation and enhancing the yield and miniaturization of semiconductor circuits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018200000001_ABST
    Figure 2025018200000001_ABST
Patent Text Reader

Abstract

To provide an oxide film layer and a surface-treatment aluminum material with excellent heat resistance, preventing cracking even at high temperatures.SOLUTION: An oxide film layer according to the present invention is characterized that it is formed on the surface of aluminum base material made of aluminum or aluminum alloy, it is amorphous in composition consisting of 73±2% (atomic number %) of oxygen and 27±2% (atomic number %) of aluminum, and no surface crack occurs under temperature conditions between 150°C and 500°C.SELECTED DRAWING: Figure 2A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxide film layer and a surface-treated aluminum material having the oxide film layer formed on its surface. [Background technology]

[0002] In general, in vacuum equipment such as CVD (Chemical Vapor Deposition) equipment, PVD (Physical Vapor Deposition) equipment, and dry etching equipment, aluminum (hereinafter referred to as Al) or Al alloy components are provided with an anodized film to ensure corrosion resistance against corrosive chlorine gas and plasma introduced into the vacuum equipment. Stainless steel has traditionally been the main material used for such vacuum equipment, but stainless steel vacuum equipment is heavy and requires extensive construction work on the foundation, and stainless steel has poor thermal conductivity and requires a long time for baking during operation. Furthermore, there is a risk that heavy metals such as chromium (hereinafter referred to as Cr), which is a component of stainless steel, may be released during the process and become a source of contamination. Therefore, there has been active development of vacuum equipment made of Al or Al alloys, which are lighter than stainless steel, have excellent thermal conductivity, and are not susceptible to heavy metal contamination. Therefore, the applicant of the present patent application invented a surface-treated aluminum material, as disclosed in Patent Document 1, in which an anodizing process is performed using an acid such as oxalic acid, and then a dense hydrated alumina coating layer is formed thereon, with the thickness of the hydrated alumina coating layer being 0.5 μm or more. Furthermore, the applicant of the present patent application has invented a surface-treated aluminum material in which the arithmetic mean roughness of the surface of the hydrated alumina coating layer is set to Ra = 10 nm or less in addition to the thickness of the layer, thereby reducing the treated surface area and improving the ability to suppress outgassing and etching resistance, and the details of this invention are disclosed in Patent Document 2. In this application, the anodized coating layer that has been subjected to a sealing treatment is called an oxide coating layer to distinguish it from the anodized coating layer. Therefore, in addition to the entire layer in which the hydrated alumina coating layer is formed on the surface of the anodized coating layer, the case in which the hydrated alumina coating layer is formed in the pores of the anodized coating layer by the sealing treatment is also called an oxide coating layer. FIG. 9A shows a scanning electron microscope (SEM) photograph (100,000 times magnification) of the surface of an oxide film layer of a conventional surface-treated aluminum material produced using the surface-treated aluminum material production method disclosed in Patent Document 2, and FIG. 9B shows a scanning electron microscope (SEM) photograph (20,000 times magnification) of a cross section of the oxide film layer of that surface-treated aluminum material. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2005-29891 A [Patent Document 2] JP 2016-194098 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, even in the case of Al or Al alloy components having an anodized coating layer and a hydrated alumina coating layer, when exposed to high temperatures, cracks occur in the oxide coating layer due to the difference in thermal expansion between the Al or Al alloy component, and particles generated from the cracks can cause defects in fine circuits formed on the surface of semiconductor wafers, etc., resulting in defects.

[0005] The present invention has been made in response to the above-mentioned conventional problems, and an object of the present invention is to provide an oxide film layer having excellent heat resistance and which does not crack even at high temperatures, and a surface-treated aluminum material. [Means for solving the problem]

[0006] In order to achieve the above-mentioned object, the oxide film layer of the first invention is formed on the surface of an aluminum base material made of aluminum or an aluminum alloy, and is amorphous in composition consisting of 73±2% (atomic %) oxygen and 27±2% (atomic %) aluminum, and is characterized in that no cracks occur on the surface under any temperature condition of 150°C to 500°C.

[0007] The surface-treated aluminum material of the second invention is characterized in that the oxide film layer of the first invention is formed on the surface of an aluminum base material made of aluminum or an aluminum alloy. Effect of the Invention

[0008] The oxide film layer according to the first aspect of the present invention has the effect that no cracks occur on its surface under any temperature condition of 150 to 500°C.

[0009] Moreover, the surface-treated aluminum material according to the second aspect of the present invention has an effect that the oxide film layer formed on the surface thereof does not develop cracks under any temperature condition of 150 to 500°C. [Brief description of the drawings]

[0010] [Figure 1] 1 is a flowchart showing steps of a method for producing a surface-treated aluminum material according to an embodiment of the present invention. [Figure 2A] 1 is a scanning electron microscope (SEM) photograph (100,000 times) of the surface of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention. [Figure 2B]1 is a scanning electron microscope (SEM) photograph (20,000 times) of a cross section of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention. [Figure 3A] 1 is a graph showing the results of glow discharge spectroscopy (GDS) analysis of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention, in comparison with a conventional general oxalic acid anodized film layer. [Figure 3B] 1 is a graph showing the results of X-ray diffraction (XRD) analysis of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention, in comparison with a conventional general oxalic acid anodized film layer. [Figure 4] FIG. 2 is a conceptual diagram showing a method for counting cracks on the surface of an oxide film layer of a surface-treated aluminum material. [Figure 5A] 1 is an enlarged photograph (50x) of the surface of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention when heated to 150° C. [Figure 5B] 1 is an enlarged photograph (50x) of the surface of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention when heated to 300° C. [Figure 5C] 1 is an enlarged photograph (50x) of the surface of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention when heated to 400° C. [Figure 5D] 1 is an enlarged photograph (50x) of the surface of an oxide film layer of a surface-treated aluminum material according to an embodiment of the present invention when heated to 500° C. [Figure 6A] This is an enlarged photograph (50x) of the surface of the oxide film layer of a conventional surface-treated aluminum material heated to 150°C, and the black circles indicate the number of cracks. [Figure 6B] This is an enlarged photograph (50x) of the surface of the oxide film layer of a conventional surface-treated aluminum material heated to 300°C, and the black circles indicate the number of cracks. [Figure 6C] This is an enlarged photograph (50x) of the surface of the oxide film layer of a conventional surface-treated aluminum material heated to 400°C, and the black circles indicate the number of cracks. [Figure 6D]This is an enlarged photograph (50x) of the surface of the oxide film layer of a conventional surface-treated aluminum material heated to 500°C, and the black circles indicate the number of cracks. [Figure 7] 1 is a graph showing a comparison of the number of cracks generated on the oxide film layer surface of a surface-treated aluminum material according to an embodiment of the present invention and a conventional surface-treated aluminum material. [Figure 8A] 1 is a graph showing a comparison of the results of measuring the dielectric breakdown voltage of a surface-treated aluminum material according to an embodiment of the present invention and a conventional surface-treated aluminum material, with the oxide film layer having a thickness of 30 μm, while changing the temperature of the oxide film layer. [Figure 8B] 1 is a graph showing a comparison of the results of measuring the dielectric breakdown voltage of a surface-treated aluminum material according to an embodiment of the present invention and a conventional surface-treated aluminum material, with the oxide film layer having a thickness of 50 μm, while changing the temperature of the oxide film layer. [Figure 9A] This is a scanning electron microscope (SEM) photograph (100,000 times) of the surface of an oxide film layer of a conventional surface-treated aluminum material. [Figure 9B] This is a scanning electron microscope (SEM) photograph (20,000x magnification) of a cross section of an oxide film layer on a conventional surface-treated aluminum material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the oxide film layer, the oxide film surface-treated aluminum material, and the method for producing the surface-treated aluminum material according to the present invention will be described with reference to Figures 1 to 7. First, the method for producing the surface-treated aluminum material will be described. FIG. 1 is a flow chart showing steps of a method for producing a surface-treated aluminum material according to an embodiment of the present invention. In FIG. 1, step S1 indicates an anodizing process, step S2 indicates a sealing process, and step S3 indicates a cleaning process as a post-processing process. When performing the anodizing treatment process in step S1, the electrolyte conditions are as shown in Fig. 1, with a total oxalic acid concentration of 30 to 45 g / L and a free oxalic acid concentration of 30 to 35 g / L, a dissolved aluminum concentration of 1.6 to 4.8 g / L (2 to 4 g / L ± 20%) or less, and an electrolyte temperature of 22 ± 5°C. The electrolyte temperature of 22 ± 5°C is set to 22°C and automatically cooled because heat is generated due to solution resistance during anodizing treatment, but the temperature fluctuates above and below the set temperature due to factors such as the threshold value of the temperature sensor, so the electrolyte temperature is set to ± 5°C from 22°C.

[0012] In step S1, an electrolytic cell is filled with the above-mentioned electrolytic solution, a cathode and an aluminum base material made of aluminum or an aluminum alloy as an anode are immersed in the electrolytic solution, and a direct current voltage of 100 to 150 V is applied to the aluminum base material and the cathode. The current density is 1.0 to 2.0 A / dm 2 The treatment time (energization time) is 120 to 60 minutes. The current density of this current is 1.0 to 2.0 A / dm 2 The current flow time of 120 to 60 minutes is the condition for making the thickness of the anodic oxide film layer 30 μm, and the current flow time of 1.0 A / dm 2 120 minutes, 2.0A / dm 2 In this case, it is 60 minutes. Therefore, when the thickness is thinner than 30 μm, the current application time can be appropriately shortened from 120 minutes or 60 minutes. Conversely, when the thickness of the anodic oxide film layer is to be a thick film of about 50 μm, the electrolyte conditions in the anodizing process in step S1 are the same as those shown in FIG. 1, and the current density of the current during the process is also the same, 1.0 to 2.0 A / dm 2 However, the current flow time is 1.0A / dm 2 240 minutes, 2.0A / dm 2 Of course, if the film thickness is 30 to 50 μm, the resistance is 1.0 A / dm 2 If so, the power supply time should be between 120 and 240 minutes, and 2.0A / dm 2If so, it is best to adjust it appropriately between 60 and 190 minutes.

[0013] In the electrolytic cell, current flows from the aluminum substrate toward the cathode, robbing it of electrons, ionizing the aluminum in the aluminum substrate and generating the aluminum ions on the surface of the aluminum substrate. In addition, oxygen is generated from the aluminum substrate (the anode) and hydrogen is generated from the cathode by the electrolysis of water, and the aluminum ions form an aluminum oxide film with multiple micropores on the surface of the aluminum substrate due to the oxygen generated. This is the anodized film layer. In this anodizing process, the reaction activity with the electrolyte is reduced by mixing the same metal ions as those in the aluminum base material of the anode; however, the concentration of dissolved aluminum in the electrolyte is lowered from the usual level of around 15 g / L to increase the reaction activity with the electrolyte, making it easier for the aluminum ions to dissolve on the surface of the aluminum base material and facilitating the formation of an aluminum oxide film.

[0014] In this embodiment, a voltage higher than normal is applied to the electrodes. In the anodizing process of the method for producing a surface-treated aluminum material of the present invention, a voltage of 100 to 150 V, which is higher than the normal applied voltage of 55 to 65 V, is applied to the electrodes, so that a larger current flows through the aluminum base material and the electrolyte, thereby increasing the Joule heat generated from the aluminum base material. That is, by applying a voltage higher than normal to the electrodes, a current larger than normal is passed, increasing Joule heat, electrically and thermally increasing the activity of the aluminum in the aluminum substrate, creating a state in which a larger amount of aluminum ions on the aluminum substrate can be dissolved into the electrolyte. These aluminum ions also fill the micropores in the aluminum oxide film. In addition, since the aluminum oxide film is an insulating film, regardless of the film thickness, as the film thickness increases during the anodizing process, the voltage begins to increase, and when the voltage exceeds the upper limit of the rectifier, the set current value begins to decrease, resulting in a certain degree of range in the current value. Above, we have explained step S1 in Fig. 1. In this process, some aluminum oxide forms an anodized film layer on the aluminum base material, and highly active aluminum ions that were not used to form the anodized film are accumulated in large quantities in the micropores of the anodized film layer. This state occurs due to a decrease in the concentration of dissolved aluminum in the electrolyte and the dissolution of a large amount of aluminum ions into the electrolyte due to the passage of high voltage current.

[0015] Next, a description will be given of step S2 in Fig. 1. Step S2 is a sealing step. In the sealing treatment according to the present embodiment, ultrapure water is heated to 150 to 180° C. and used as saturated water vapor. The sealing treatment, together with the subsequent cleaning process in step S3, causes some of the aluminum oxide, which is a component of the anodized film layer, to absorb moisture and become boehmite (Al 2 O 3 H 2 O) and bayerite (Al 2 O 3 3H 2 O), which expands and seals the inner walls of the micropores in the anodized film layer, improving the crack resistance of the surface-treated aluminum material. In this embodiment, first, in step S2, the aluminum base material having the anodized coating layer formed in step S1 is exposed to saturated water vapor at 150 to 180°C for a short period of time, such as at least 1 minute but not exceeding 5 minutes. According to such step S2, a hydrated alumina coating layer made of hydrates can be formed inside the micropores. Generally, as disclosed by the applicant of the present application in JP 2005-29891 A, it is known that the inside of the micropores and the surface of the anodized coating layer can be covered with a hydrated alumina layer by extending the sealing time, but in the present invention, a hydrated alumina coating layer is formed inside the pores by exposing to a high temperature for a short time, and the treatment is completed before the excess hydrates from inside the micropores come out to the surface, thereby obtaining an oxide coating layer without a hydrated alumina coating layer on the surface as shown in FIG. 2A. In addition, even if the film thickness is increased to 50 μm or is 30 μm or less, the processing conditions for the sealing step in step S2 are the same, and the processing conditions for the cleaning step in step S3 described later are also the same. For example, the treatment time in step S2 is a short time of 1 minute or more and not exceeding 5 minutes, which is a time that does not change depending on the thickness of the formed anodic oxide coating layer. If the time is longer, the amount of hydrates seeping out to the surface increases, making it easier for crystallization to occur on the surface, which can lead to cracks, so the sealing treatment is performed for a short time regardless of the film thickness.

[0016] Next, step S3 is a cleaning step using pure water as a post-sealing step. In step S3, the aluminum base material having the oxide film layer after the sealing treatment in step S2 is exposed to pure water at room temperature (5 to 30° C.) for 5 minutes or more. By carrying out step S3, it is possible to remove excess unreacted hydrates from inside the micropores. The unreacted hydrates inside the micropores come to the surface of the oxide film layer by immersing in low-temperature pure water, and are then removed. At this time, it is important to treat at a low temperature, since if the temperature of the pure water is high, a hydrated alumina film layer will form on the surface, and the water washing time should be appropriately extended as the film thickness increases in order to remove the unreacted hydrates. In this manner, the surface-treated aluminum material according to the embodiment of the present invention is manufactured.

[0017] Moreover, what is formed on the surface of this surface-treated aluminum material is an oxide film layer according to the embodiment of the present invention. FIG. 2A shows an SEM photograph (100,000 times magnification) of the surface of the oxide film layer of the surface-treated aluminum material, and FIG. 2B shows an SEM photograph (20,000 times magnification) of the cross section of the oxide film layer. In particular, from Figure 2A, it can be seen that holes with diameters of about several tens of nm have been formed on the surface of the oxide film layer based on the scale shown under the frame of the photograph, and that the hydrated alumina film layer that was formed on the surface of the conventional oxide film layer shown in Figure 9A is not present. Furthermore, when comparing FIG. 2B with FIG. 9B, a hydrated alumina coating layer having a thickness of about 0.8 μm can be seen on the surface of the conventional oxide coating layer (FIG. 9B), i.e., the oxalic acid anodized coating layer, based on the scale displayed under the frame of the photograph, whereas a faint shadow-like substance having a thickness of about 0.2 μm can be seen in the oxide coating layer according to the embodiment of the present invention (FIG. 2B). However, when considered together with the surface photograph of FIG. 2A, it is believed that the hydrated alumina coating layer is not formed on the surface, but exists within and seals the holes formed in the anodized coating. In order to confirm this, an unsealed coating layer of a general oxalic acid anodized aluminum and an oxide coating layer according to the present embodiment were subjected to an alkali resistance test specified in JIS (H8681-1) and compared. Note that since this is a general unsealed coating layer of an oxalic acid anodized aluminum, it is referred to as an anodized coating layer in this application. The time it takes for corrosion to reach the aluminum base for a typical oxalic acid anodized coating layer is 29.6 seconds (average value of five points), and when an alkali resistance test was similarly performed on the oxide coating layer according to this embodiment, the time it takes for corrosion to reach the aluminum base was 147.7 seconds (average value of five points). Comparing the times, it took about five times longer for corrosion to reach the aluminum base for the oxide coating layer according to this embodiment. This is thought to be because the insides of the pores in the oxide coating layer according to this embodiment are sealed with a hydrated alumina coating, which slows down the progression of corrosion and increases the time it takes. The thickness of the conventional oxide film layer shown in FIG. 9B was about 50 μm not including the hydrated alumina film on the surface, while the thickness of the oxide film layer according to the present embodiment shown in FIG. 2B was about 50 μm.

[0018] Furthermore, the results of analyzing the components of the oxide film layer according to this embodiment will be described with reference to Fig. 3A. Fig. 3A is a graph showing the glow discharge spectroscopy (GDS) analysis results of the oxide film layer of the surface-treated aluminum material according to this embodiment in comparison with a conventional general oxalic acid anodized film layer. In Figure 3A, the horizontal axis indicates the thickness (depth) of the oxide film layer [μm], with 0.0 on the left side indicating the surface of the oxide film layer, and the vertical axis indicates the oxygen and aluminum [atomic percentage]. From the results shown in Fig. 3A, it can be seen that the oxide film layer according to this embodiment has a lower oxygen concentration than a typical oxalic acid anodized film layer. Specifically, the oxygen concentration is about 73-75% at a depth of 2 µm or more and 5 µm or less from the film layer surface. Conversely, it can be seen that the aluminum concentration is higher in the oxide film layer than in a typical oxalic acid anodized film layer. Specifically, the aluminum concentration is about 25-27% at a depth of 2 µm or more and 5 µm or less from the film layer surface. The results of analyzing the structure of the oxide film layer according to the present embodiment will be described with reference to Fig. 3B, which is a graph showing the results of X-ray diffraction (XRD) analysis of the oxide film layer of the surface-treated aluminum material according to the embodiment of the present invention in comparison with a conventional general oxalic acid anodized film layer. In FIG. 3B, the horizontal axis represents the diffraction angle (2θ [°]) and the vertical axis represents the diffraction intensity [cps]. Although both the oxide coating layer according to the present embodiment and the conventional oxalic acid anodized coating layer have an anodized aluminum structure, the results shown in Fig. 3B show that the diffraction intensity peak at a diffraction angle of 26 to 27° of the oxide coating layer according to the present embodiment is shifted to the left compared to the peak of the conventional oxalic acid anodized coating layer. This proves that the spacing between atoms is wider. It can also be seen that the diffraction intensity of the oxide coating layer according to this embodiment is higher than the diffraction intensity of the conventional oxalic acid anodized coating layer over the entire range of diffraction angles. This is believed to be because the scattered X-rays of the oxide coating layer are more intensified than those of conventional oxalic acid anodized coating. Although both the oxide coating layer according to this embodiment and the oxalic acid anodized coating layer are amorphous (non-crystalline), the oxide coating layer according to this embodiment is believed to have a higher crystallinity.

[0019] From the GDS analysis results shown in FIG. 3A and the XRD analysis results shown in FIG. 3B, the oxide film layer according to the present embodiment has a crystal structure with a low oxygen concentration and a long distance between atoms, and therefore, even when heated to 500° C., there are no cracks (fractures) on the film surface (fractures per 4 mm). 2That is, it was found to be a heat-resistant oxide film layer in which no cracks were generated.

[0020] Next, a method for measuring the heat resistance of the oxide film according to the present embodiment in comparison with a conventional oxide film will be described. First, a method for measuring the number of cracks generated by heating an oxide film in order to measure the heat resistance of the oxide film will be described with reference to FIG. In Figure 4, the area enclosed by the square is a rectangular area of ​​2 mm in length and width, and the straight lines drawn within it are cracks. The cracks are counted as follows: if a crack that occurs within the measured range is independent and not connected to other cracks, such as the first or second line, it is counted as one crack; if a crack that occurs within the measured range butts up against only one other crack, such as the third or fourth line, it is counted as one crack; if a crack that occurs within the measured range stops other cracks and connects to them, such as the fifth line, the area between the connected points is also counted as one crack; and if a crack that occurs within the measured range stops other cracks and connects to them, such as the sixth or seventh line, it is counted as one crack from the connected point to the end of the measured range. In the present application, the cracks measured in this manner are represented by black circles so that they can be easily counted.

[0021] Using this measurement method, the oxide film according to the embodiment of the present invention and a conventional oxide film were heated to 150° C., 300° C., 400° C., and 500° C., and the number of cracks that occurred was measured. 5A to 5D are examples of enlarged photographs (50x) of the oxide film layer surface of a surface-treated aluminum material according to an embodiment of the present invention when heated to 150° C., 300° C., 400° C., and 500° C. As is clear from the photographs in Fig. 5A to 5D, zero cracks were generated, that is, no cracks were generated in any of the samples. The reason why the magnification was selected to be 50x is because the viewing area becomes smaller if the magnification is increased beyond this. For example, if the magnification is set to 100x, the viewing area becomes small (1mm x 1mm), and it may be difficult to track the actual number of cracks. The thickness of the oxide film layer is 30μm. Figures 6A to 6D are examples of enlarged photographs (50x) of the surface of a conventional oxide film layer when heated to 150°C, 300°C, 400°C, and 500°C, respectively. The black dots indicate the cracks counted one by one, and it can be seen from these figures that the number of cracks increases as the temperature rises from 150°C to 500°C. The thickness of this conventional oxide film layer (a typical oxalic acid anodized film layer) is also 30μm. 7 is a graph showing a comparison of the number of cracks generated on the oxide film layer surface of the surface-treated aluminum material according to the embodiment of the present invention and the conventional surface-treated aluminum material, with respect to the overall measurement results including the measurement results in Figures 5A to 5D and 6A to 6D. The horizontal axis is the heating temperature (°C) and the vertical axis is the number of generated cracks. Table 1 summarizes the average values ​​of all the measurement results shown in FIG. In addition, A6061-T6 in the table refers to an alloy of aluminum containing magnesium and silicon that has been subjected to T6 treatment.

[0022] [Table 1]

[0023] As shown in FIG. 7 and Table 1, compared to the conventional oxide film layer, the oxide film layer according to the present embodiment has a crack generation rate of 4 mm at temperatures between 150° C. and 500° C. 2 In addition, in the conventional oxide coating layer, the number of cracks increases significantly from 400°C to 500°C compared to 300°C to 400°C. However, no cracks were generated in the oxide coating layer of the present embodiment, which shows that the oxide coating layer has extremely high heat resistance. Furthermore, although this measurement was performed with an oxide film layer thickness of 30 μm, the occurrence of cracks was also confirmed for thicker films, including those with a thickness of 50 μm, by methods other than visual inspection, specifically by measuring the dielectric breakdown voltage, as described below.

[0024] 8A and 8B are graphs showing the results of measuring the dielectric breakdown voltage according to the temperature change when the temperature of the oxide film layer is changed, with the thickness of the oxide film layer (general oxalic acid anodized film layer) of the surface-treated aluminum material according to the embodiment of the present invention and that of the conventional surface-treated aluminum material being set at 30 μm and 50 μm, respectively. The measurements were made for two groups (A and B) under the same conditions. The method for measuring the dielectric breakdown voltage is specified in the JIS standard (H8687) as follows: a voltage is applied to each oxide film layer at a ramp rate of 25 V / sec, the circuit breaking current is set to 5 mA, and the voltage at that point is taken as the dielectric breakdown voltage. Using this JIS method, the dielectric breakdown voltage was measured at 25°C, and then the product of the present invention was heated, cooled, and reheated in the following order: 150°C, 300°C, 400°C, 500°C, 25°C, 150°C, and 300°C, and the dielectric breakdown voltage was measured at each temperature. However, although the JIS regulations state that measurements should be made in an environment ranging from 5 to 35°C, this time the dielectric breakdown voltage was measured during heating in order to investigate the relationship between the occurrence of cracks and temperature. If cracks occur due to heating, current will flow more easily and the breakdown voltage will decrease. If the measured value at 25°C is the same as the measured value at the heating temperature, it means that no cracks have occurred due to heating.

[0025] For comparison, the dielectric breakdown voltage of a general anodized aluminum film with oxalic acid was also measured under the same conditions. The measurement results are shown in Figures 8A and 8B. Since the dielectric breakdown voltage is proportional to the thickness of the oxide film layer, measurements were made at two film thicknesses, 30 μm and 50 μm. In the product of the present invention (the oxide film layer according to the present embodiment), no change is observed in the measured values ​​of the dielectric breakdown voltage at 25°C, 150°C, 300°C, and 400°C for both A and B in the two film thicknesses, but the value is halved at 500°C. This is not due to the occurrence of cracks in the oxide film layer, but is considered to be due to a decrease in the electrical resistance value of the oxide film layer itself. The reason for this is that when cooled to 25°C and remeasured, the dielectric breakdown voltage value is restored to the same level as the initial measurement at 25°C, which can be understood to mean that no cracks have occurred in the oxide film layer itself. Moreover, from the drop in the dielectric breakdown voltage of the product of the present invention at about 500° C. mentioned above, it was found that the oxide film layer has semiconductor-like properties in that its electrical resistance decreases at that temperature. On the other hand, in the case of the oxalic acid anodized coating layer used as the comparative example, the breakdown voltage dropped sharply from 25° C. This is thought to be because cracks appeared on the coating surface due to heating, and the cracks became paths for current, causing the measured value to drop. As with the product of the present invention, the dielectric breakdown voltage was measured after heating to 500°C and then cooling to 25°C, but the value remained low and did not recover to the value initially measured at 25°C. Therefore, it is believed that the initial heating to 150°C caused numerous cracks to form on the surface of the oxide film layer, and the value did not return to the original value even after cooling.

[0026] As explained above, in the case of the product of the present invention, the temperature returned to the initial value at 25° C., and it is believed that this provides electrical proof that no cracks have occurred. In addition, Fig. 8B shows the results of measuring the dielectric breakdown voltage of the oxide film layer of the present invention and the conventional oxide film layer under the same test conditions with a film thickness of 50 μm. The dielectric breakdown voltage is high because the film thickness is thick, but the effect of heating is not observed in the case of the present invention. As in the case of the 30 μm film thickness, a drop in the measured dielectric breakdown voltage is observed around 500°C, but the measured value when cooled to 25°C is similar to the initial measured value at 25°C. From this figure, it can be seen that the present invention does not experience cracks due to heating up to 500°C even with a film thickness of 50 μm.

[0027] Through their first attempt at measuring the dielectric breakdown voltage during heating, the inventors were able to confirm that the conventional oxalic acid anodized coating layer had poor insulation properties and could not obtain a stable plasma due to the heating during plasma etching, which is essential for semiconductor circuits. On the other hand, the product of the present invention was able to obtain a stable breakdown voltage even at high temperatures. As explained above, the results of this test showed that in the oxide coating layer according to this embodiment, regardless of whether the film thickness was 30 μm or 50 μm, no cracks occurred at any temperature between 150° C. and 500° C., but also showed that no cracks occurred at any temperature or in any temperature range between 150° C. and 500° C. Furthermore, since cracks are less likely to occur when the film thickness is thinner, it is believed that no cracks will occur in the oxide film layer according to this embodiment if the film thickness is at least 50 μm or less.

[0028] As described above, the surface-treated aluminum material produced by the method for producing a surface-treated aluminum material according to this embodiment and the oxide film formed on the surface thereof are capable of exhibiting superior heat resistance to conventional surface-treated aluminum materials, and it can be said that cracks hardly occur even in high temperature regions. Therefore, since there are no particles generated from the cracks, even when the material is introduced into a vacuum device such as a CVD device, a PVD device or a dry etching device, a phenomenon in which particles adhere to the surface of a semiconductor wafer, etc., does not occur. Furthermore, the material can withstand high temperatures even in the etching process when producing semiconductor circuits and can emit plasma stably, so that it is possible to exhibit the excellent effect of improving the yield of produced ICs (integrated circuits) and ensuring further miniaturization of semiconductor circuits. In the manufacturing process of large-capacity memory, a large-capacity memory circuit is manufactured in a small area by stacking memory circuits in multiple layers in a vertical direction called 3D NAND. However, since the circuit deposition process and dry etching process are repeated many times, the heat generated during etching is trapped, and the temperature of the manufacturing equipment surface rises to about 300°C. The temperature rise causes cracks in the anodized film layer, which generates particles that fall on the deposited circuit and break the nanometer-wide memory circuit. However, by using the oxide film layer and surface-treated aluminum material according to the present embodiment, no particles are generated, and the yield can be significantly improved in the production of large-capacity memory. Small, large-capacity memories are essential in all industrial fields, such as smartphones, data servers, self-driving devices, and online video distribution, and therefore the effects of adopting the oxide coating layer and surface-treated aluminum material according to the present embodiment can have a significant positive impact on many industrial infrastructures. Furthermore, with the method for manufacturing a surface-treated aluminum material according to the present embodiment, it is possible to easily manufacture a surface-treated aluminum material having an oxide film formed on its surface, which is capable of exerting the excellent effects described above. [Industrial Applicability]

[0029] The present invention can be used not only as an inner wall material for vacuum equipment such as CVD equipment, PVD equipment, and dry etching equipment, which are required to minimize particle generation, particularly under high temperatures, but also in a wide range of general applications such as building materials, light electrical components, and automobile parts.

Claims

1. An oxide coating layer characterized in that it is formed on the surface of an aluminum substrate made of aluminum or an aluminum alloy, the oxide coating layer is amorphous and has a composition of 73±2% (atomic %) oxygen and 27±2% (atomic %) aluminum, and no cracks occur on the surface under any temperature condition of 150°C to 500°C.

2. 2. A surface-treated aluminum material, comprising the oxide film layer according to claim 1 formed on a surface of an aluminum substrate made of aluminum or an aluminum alloy.

Citation Information

Patent Citations

  • Surface structure of aluminum member and manufacturing method therefor

    JP2017160533A

  • Anodized aluminum member, and manufacturing method and treatment agent of anodized aluminum member

    JP2019081963A

  • Surface-treated aluminum material, and its production method

    JP2005029891A

  • Surface-treated aluminum material and method for producing the same

    JP2016194098A